Management of Marfan Syndrome, with a Specific Focus on the Significance of Physical Activity in this Patient Population - Jędrzejewska-Rzezak, Patrycja (Quality in Sport, 2025)
Introduction: Marfan syndrome is an autosomal dominant disorder of connective tissue. Timely diagnosis and effective therapy are essential for individuals with Marfan syndrome, as they are susceptible to severe cardiovascular consequences, including aortic aneurysms and aortic dissection. The conventional treatment comprises beta-blockers to mitigate the dilatation of the aorta and aortic surgery. The efficacy of contemporary medicinal and surgical interventions in Marfan syndrome has significantly enhanced mean life expectancy. International guidelines generally discourage physical activity for individuals with Marfan syndrome. Recent recommendations have created exclusions for these patients, indicating benefits from engaging in low-intensity physical activity exclusively. Aim of the study: The primary aim of this research is to elucidate the most recent management ideas pertaining to Marfan syndrome. Significant emphasis is placed on the importance and safety of physical activity in individuals afflicted with this disease. The risks linked to physical activity are addressed, however the advantages of particular activities are highlighted. Materials and methods: A review of the literature available in the PubMed database was performed, using the key words: „Marfan syndrome", „connective tissue disease”, „physical activity", „aortic aneurysm”, „FBN1”. Conclusion: The prognosis for patients with Marfan syndrome has markedly improved in the last years. Contrary to conventional guidance to refrain from physical activity, emerging research indicates that low-intensity exercise may be advantageous. Research on the safety and health implications of physical activity in patients with Marfan syndrome is exceedingly few. Current information indicates that moderate physical activity at a particular intensity may be safe in this condition. Additional study is necessary to offer targeted recommendations for patient training and enhance their long-term quality of life.